MENGINTEGRASIKAN METODOLOGI HUKUM SUNNI KLASIK KE DALAM PEMIKIRAN EKONOMI ISLAM KONTEMPORER - Riyan Damara Putra; Moh. Bahrudin; Syamsul Hilal (KASBANA, 2026)
Abstract This study aims to examine how classical Sunni legal methodologies in usul al-fiqh can be systematically integrated into the development of contemporary Islamic economic thought. The analysis is grounded in the central problem that modern Islamic economic practices often rely on fragmented or overly textual approaches, despite the rich methodological traditions of the Hanafi, Maliki, Shafi‘i, and Hanbali schools. Using a qualitative descriptive–analytical method based on doctrinal review, this research explores authoritative classical texts alongside contemporary regulatory documents, including DSN–MUI fatwas, to assess the relevance of qiyas, istihsan, maslahah-oriented reasoning, contractual clarity, and maqasid-based considerations for present-day economic governance. The findings indicate that the methodological strengths of the four schools can be synthesized to provide a coherent normative and practical foundation for addressing modern economic issues such as digital transactions, ethical finance, and sustainability. The study demonstrates that the integration of classical jurisprudential principles not only strengthens the legitimacy of Islamic economic policies but also enhances their adaptability to emerging challenges. This research contributes by offering an analytical framework that connects the epistemology of Islamic legal theory with contemporary policy formation, thereby promoting an Islamic economic system that is both principled and responsive to societal needs. Keywords : DSN-MUI, Islamic Economics, Sunni School of Law, Islamic Legal Methodology, Usul al-Fiqh